Improving Self-Efficacy of Madrasah Aliyah Miftahul Jannah’s Students in Foreign Language Acquisition - Afifah, Lia Jauharotul (ANFA MEDIATAMA, 2024)
Students with low motivation refer to students with low self-efficacy which means they do not believe in themselves in achieving goals. This research used the descriptive qualitative method where the author described the situation in the Madrasah Aliyah (MA) Miftahul Jannah In developing students’ self-efficacy. The finding showed that to improve the students’ self-efficacy, the author conveys the steps the teacher can take to help students improve their self-efficacy through authentic learning. Authentic learning should be used in foreign language teaching instead of conventional activities. Using authentic materials can motivate students and help them feel comfortable using a foreign language. Thus, foreign language teachers should assist students in engaging in constructive learning environments with authentic materials. The use of authentic materials should be emphasized when training potential foreign language teachers so that future teachers can demonstrate the use of authentic materials by improving students’ self-efficacy. Moreover, teachers can help students set clear goals in learning a foreign language and provide honest feedback. In that way, teachers had a chance to see the differences in students’ self-efficacy in learning a foreign language. The aim of the present review of literature is to focus on the improvement of students’ self-efficacy in foreign language acquisition.